2011
DOI: 10.1007/s10654-011-9594-1
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic variations in mortality in pre-school children in Denmark, 1973–2004

Abstract: The objective of the study was to describe ethnic differences in under-five-years mortality in Denmark according to maternal country of origin. We conducted a large registry-linkage study of all singleton live-born children from mothers born in Denmark and from the ten largest migrant groups (n=1.841.450). Study outcomes were death before the age of five years from all causes combined and the most frequent death causes. Results showed that children of mothers of Turkish, Pakistani, Somali and Iraqi origin had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The highest risk was found in the group of ‘severe and profound intellectual disability’. The results of this report support the hypothesis that consanguinity may play a role in the disparities of health in Danish‐born children of women with different countries of origin …”
Section: Commentsupporting
confidence: 83%
See 2 more Smart Citations
“…The highest risk was found in the group of ‘severe and profound intellectual disability’. The results of this report support the hypothesis that consanguinity may play a role in the disparities of health in Danish‐born children of women with different countries of origin …”
Section: Commentsupporting
confidence: 83%
“…Considerable disparities in perinatal, infant, and under 5‐year mortality (U5‐mortality) have been observed between children born in Denmark in the period from 1973 to 2004 by mothers who migrated to Denmark from Afghanistan, Iraq, Pakistan, Somalia, and Turkey when compared with the majority of the population. The increased mortality was apparently not explained by differences in indicators of parental socio‐economic position . Higher childhood mortality rates among some ethnic minorities are well described in many Western countries, but the underlying causes behind these disparities are not fully established .…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…However, in this study country of origin was not taken into account. It has been shown that reproductive and child health are diverging among the different migrant groups in Denmark [19, 20], and to understand the mechanisms behind the potential increased vulnerability of the migrant groups, it is important not to treat migrants as one entity. Therefore, in order to guide future preventive strategies, we find it justified that a better understanding of patterns in breastfeeding prevalence and the mechanisms behind will be obtained using a country of origin approach.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent Danish studies have found ethnic disparities within perinatal, infant and early child mortality 1,2 . Both studies looked at differences among the largest immigrant groups and found that some immigrant women experience similarly, some even better, although a large majority worse pregnancy outcomes when compared with Danish‐born women.…”
mentioning
confidence: 99%